1993
DOI: 10.1136/gut.34.6.762
|View full text |Cite
|
Sign up to set email alerts
|

A study of the pathogenesis of Helicobacter pylori negative chronic duodenal ulceration.

Abstract: In the past five years 12 patients have been identified presenting with chronic duodenal ulcer (DU) disease and with no evidence of current or recent Helicobacter pylori (H pylori) infection. Four of them were taking regular non-steroidal anti inflammatory agents, one was subsequently found to have Crohn's disease of the duodenum, and one to have the Zollinger-Ellison syndrome. The remaining six patients with idiopathic DU disease were remarkable for their absence of the A1 blood antigen gene. Detailed studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(61 citation statements)
references
References 21 publications
2
57
1
1
Order By: Relevance
“…That is, the prevalence of H. pylori-negative peptic ulcers in the USA and Australia is relatively high, at 27-43%, and relatively low in Europe and Japan, at 2.7-8.0% [31][32][33][34][35][36]. This could be explained from the fact that the infection rate of H. pylori fell more rapidly in the USA and Australia.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the prevalence of H. pylori-negative peptic ulcers in the USA and Australia is relatively high, at 27-43%, and relatively low in Europe and Japan, at 2.7-8.0% [31][32][33][34][35][36]. This could be explained from the fact that the infection rate of H. pylori fell more rapidly in the USA and Australia.…”
Section: Discussionmentioning
confidence: 99%
“…pylori-negative duodenal ulcer was only rare by 2.8-6.0% in developed countries in the early 1990's (Table 1) (2,3), approximately half of these were NSAID-associated ulcers. Therefore, idiopathic duodenal ulcers, which are not associated with H. pylori or NSAIDs, were extremely rare at 0.3-1.4% (2,3). Recent studies have shown a higher incidence of idiopathic duodenal ulcers in USA and Australia, while the incidence of such an ulcer is still reportedly low in other countries, including Japan (Table 2).…”
Section: Is H Pylori Really a Cause Of Pud?mentioning
confidence: 99%
“…pylori, eg. in Crohn's disease, following ingestion of NSAIDs [44], and in the Zollinger-Ellison syndrome [45]. It seems logical to eradicate H .…”
Section: Duodenal Ulcermentioning
confidence: 99%